COMMUNITY DEVOTION IMPLEMENTATION WARM COMPRESS MEASURES FOR JUNIOR HIGH SCHOOL STUDENTS NUR LIGHT OF AN EXPERIENCED FIELD DISMINORE - Purwaningsih, Purwaningsih; Sinuraya, Evamona; Pamela, Tia; Banjarnahor, Hotma Ria (LPPM Institut Pendidikan Nusantara Global, 2024)
Dysmenorrhea is defined as pain during menstruation. The word dysmenorrhea (dysmenorrhea) comes from ancient Greek (Greek) which comes from dys which means difficult, painful, abnormal. Meno means moon, and rrhea means flow. So dysmenorrhoea can be interpreted as difficult menstrual flow or pain during menstruation (Haerani, 2020). Dysmenorrhea is pain during menstruation, usually characterized by a sinking feeling centered in the lower abdomen. Complaints related to menstrual pain can vary from mild to severe. The level of menstrual pain is directly related to the length of menstruation and the amount of blood during menstruation. Menstruation is almost always followed by heartburn or pain (Husna 2018). This activity will be held on August 23 2023. The number of participants was 25 Nur Cahaya Medan Selayang Middle School students. The results of the service activities showed that in the pretest questionnaire the participants' level of knowledge was found to be in the good category as many as 8 people (32.0%), in the sufficient category as many as 10 people (40.0%), and in the poor category as many as 7 people (28.0%). The results of the posttest questionnaire on the level of participants' knowledge showed that there were 15 people in the good category (60.0%), 8 people in the sufficient category (32.0%), and 2 people in the poor category (8.0%).